Ferri-obertiite from the Rothenberg quarry, Eifel volcanic complex, Germany: mineral data and crystal chemistry of a new amphibole end-member. (1st May 2017) - Oberti, Roberta; Boiocchi, Massimo; Hawthorne, Frank; Ball, Neil; Blass, Güter
Pink-orange crystals of a composition within the ferri-obertiite compositional space were found in vesicles in a pale beige silicate vein found from a basalt quarry at Mount Rothenberg, Eifel district, Germany. Associated minerals are potassic feldspar, alpha quartz paramorphic after beta quartz, eifelite (the second occurrence after the Caspar quarry at Bellerberg volcano, Eifel region), tridymite, rutile, roedderite and other amphiboles. The ideal formula of ferri-obertiite is ANaBNa2C(Mg3Fe3+Ti)TSi8O22 WO2; the empirical formula derived for the holotype specimen from Mount Rothenberg from the results of electron-microprobe analysis and single-crystal structure refinement is A(Na0.76K0.22)∑0.98B(Na1.61Ca0.35Mn0.042+)∑2.00C(Mg3.58Mn2+0.11Fe3+0.62Ti4+0.66Cr3+0.01Zn0.01Ni0.01)∑5.00T(Si7.82Ti4+0.12Al0.06)∑8.00O22W[O1.26F0.55(OH)0.19]∑2.00. The unit-cell dimensions are a = 9.7901(7), b = 17.9354(13), c = 5.2892(4) Å, β= 104.142(2)°, V = 900.58 (11) Å3. The space group is C2/m, Z = 2. Ferri-obertiite is biaxial (+), with α = 1.664, β = 1.680, γ = 1.722, all ±0.002 and 2V (meas.) = 66.4(3)o, 2V (calc.) = 64.7o. The strongest eight reflections in the powder X-ray pattern [d values (in Å), I, (hkl)] are: 2.704, 100, (151); 3.116, 76, (310); 3.388, 72, (131); 8.931, 72, (110); 2.529, 67, (202); 2.583, 39, (061); 2.160, 38, (261); 3.260, 37, (240). Both the mineral and the name have been approved by the Commission on New Minerals, Nomenclature and Classification of the International Mineralogical Association (IMA 2015-079); the rock specimen has been deposited at the Museo di Mineralogia, Dipartimento di Scienze della Terra e dell'Ambiente, Università degli Studi di Pavia, under the code 2015-02.